Pharmacological interventions on smoking cessation: A systematic review and network meta-analysis - Shang, Xue; Guo, Kangle; E., Fenfen; Deng, Xinxin; Wang, Yongsheng; Wang, Ziyi; Wu, Yanan; Xu, Meng; Yang, Chaoqun; Li, Xiuxia; Yang, Kehu (Frontiers in Pharmacology, 2022)
Objective: A network meta-analysis based on randomized controlled trials was conducted to investigate the effects of pharmacological interventions on smoking cessation. Methods: English databases were searched to obtain randomized controlled trials reporting the effect of pharmacological interventions on smoking cessation. The risk of bias for the included trials was assessed using Cochrane Handbook tool. Stata 15.1 software was used to perform network meta-analysis, and GRADE approach was used to assess the evidence credibility on the effects of different interventions on smoking cessation. Results: A total of 159 studies involving 60,285 smokers were included in the network meta-analysis. The analysis involved 15 interventions and which yielded 105 pairs of comparisons. The results showed that varenicline monotherapy was superior in achieving smokers to quit smoking compared to naltrexone (OR = 2.61, 95% CI [1.64, 4.16]), nicotine replacement therapy (OR = 1.42, 95% CI [1.16, 1.73]), clonidine (OR = 2.25, 95% CI [1.15, 4.39]), bupropion (OR = 1.52, 95% CI [1.22,1.89]), and placebo (OR = 2.58, 95% CI [2.22,3.01]). Furthermore, compared to above monotherapies, an evident abstinence superiority was found in varenicline plus bupropion, nicotine replacement therapy plus varenicline. Finally, the surface under the cumulative ranking curve value indicated that nicotine replacement therapy plus mecamylamine had the greatest probability of becoming the best intervention. Conclusion: Most pharmacological interventions demonstrated a benefit in smoking cessation compared with placebo, whether monotherapy or combination therapy. Moreover, confirmed evidence suggested that some combination treatments, such as varenicline plus bupropion and nicotine replacement therapy plus mecamylamine have a higher probability of being the best smoking cessation interventions.